Few-mode vertical-cavity surface-emitting lasers for space-division multiplexing *Project supported by the National Basic Research Program of China (No. 2014CB3400102), the National Natural Science Foundation of China (No. 61335004), the National High Technology Research and Development Program of China (No. 2015AA017101), and the National Key Technologies R & D Program of China (No. 2016YFB0400603). (September 2017) - Su, Yaman; Yu, Lijuan; Guo, Xia; Zhang, Xing; Liu, Jianguo; Zhu, Ninghua
Abstract: In order to choose the proper radius of oxide aperture for few-mode vertical-cavity surface-emitting lasers (VCSELs), the influences of oxide aperture size on the multi-transverse-mode behaviors are investigated in detail. By establishing the effective refractive index model to simulate VCSELs with different radii of oxide apertures, the wavelength and corresponding order of different modes are obtained. VCSELs with three kinds of oxide apertures are manufactured. Then the multi-transverse-mode spectra and near-field are measured. It is found that when the radius is between 1.5 and 4.5 μ m, few-mode VCSELs can be implemented. The 2.5 μ m VCSEL manufactured in this paper only emits LP01 mode and LP21 mode. Since the space distance between the two modes is 2 μ m, it is expected to realize direct-modulation few-mode VCSELs by channel etching or ion implantation between the two modes.